Analisis Upaya Menurunkan Cacat Produk Crank Case LH pada Proses Die Casting dengan Metode PDCA dan FMEA di PT. Suzuki Indo Mobil/Motor - Agustinus Yunan; Dimas Raya; Rifda Ilahy Rosihan (Journal of Industrial and Engineering System, 2020)
Suzuki Indo Mobil / Motorcycle is the largest motorcycle manufacturing industry in Indonesia today. Die Casting is one of the departments that is important in the manufacture of motorcycle parts. In the Die Cating section, there are a number of types of defects that exceed the company tolerance standards. During the February to July period, 228 pcs of defect products were found. For this reason, it is necessary to determine the most dominant factor in the occurrence of defects and determine the proposed improvement of the root problem. PDCA is a useful tool for continuous improvement and FMEA or Failure Mode Analysis is a tool that is often used in quality improvement methods. FMEA serves to determine the consequences of failure associated with failure in the Crank Case LH. There are three types of defects found, namely Chipped, Cracked, Wrinkled. With pareto diagram, it is known that there are three types of defect Crank Case LH which are the most dominant, namely: 9.9% chipped, Crack 6.75%, Wrinkles 4.72%. aluminum & mold is too low, engine filling time is too long, Crank Case LH Cracks the surface of the rough molding machine, engine pressure is too large, Crank Case LH Machine wrinkles Less pressure. Improve made is to make a standard number of Crank Case LH setting parameters of the engine and required SOP.